Mindfulness and its influence on quality of life and immune response in women with breast cancer - Kosz, Katarzyna; Zielińska, Martyna; Zarankiewicz, Natalia; Kuchnicka, Aleksandra; Aleksandrowicz, Jakub; Książek, Katarzyna; Mojsym-Korybska, Sylwia (Journal of Education, Health and Sport, 2019)
Mindfulness therapy is a psychological process, which main purpose is to concentrate attention on internal and external stimuli in the present moment. Practising mindfulness is correlated with well-being, greater energy and enthusiasm as well as the ability to cope with stressful situations. Breast cancer accounts for 22% of all malignant tumors in women. It is characterized by the highest mortality rate among all malignancies in this group. Diagnosis, applied treatment and changes in the women’s lifestyle may have a negative impact on their psyche. Symptoms such as depression, anxiety and fatigue often appear in patients diagnosed with breast cancer. These can lead to a decreased well-being and lower quality of life. Studies show that Mindfulness-Based Stress Reduction (MBSR) therapy has a positive impact on the quality of life of patients suffering from breast cancer. What is more, those patients may have a worse immune response and less natural killers cells activity (NKCA) than people who doesn not have a cancer disease. MBSR can re-establish NKCA and improve immune response. Patients who have noticed an improvement in their well-being during and after MBSR therapy showed higher NKCA. There is no doubt that MBSR therapy reduces the level of fatigue, depression and anxiety. Moreover, patients who undergo MBSR therapy are less afraid of a relapse and have less reactivity to the emotional stress.